2022
DOI: 10.1177/1357633x221098904
|View full text |Cite
|
Sign up to set email alerts
|

A physical therapist and nurse practitioner model of care for chronic back pain using telehealth: Diagnostic and management concordance

Abstract: Introduction Virtual care using videoconference links between urban-based physical therapists and nurse practitioners in rural primary care may overcome access challenges and enhance care for rural and remote residents with chronic low back disorders (CBD). The purpose of this study was to evaluate the concordance of this new model of care with two traditional models. Methods In this cross-sectional study design, each of 27 participants with CBD were assessed by: 1) a team of a nurse practitioner (NP) located … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Additionally, experience with telephysical therapy has been improved due to the COVID-19 pandemic [ 24 ]. One recently reported care model for non-operative back pain includes a partnership of a rural nurse practitioner and an urban physical therapist providing care via telehealth [ 25 ]. To maximize the reach and sustainability of such measures, equitable insurance coverage should be available for the full spectrum of pain treatments, particularly as insurance initiatives have been shown to impact pain care access [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, experience with telephysical therapy has been improved due to the COVID-19 pandemic [ 24 ]. One recently reported care model for non-operative back pain includes a partnership of a rural nurse practitioner and an urban physical therapist providing care via telehealth [ 25 ]. To maximize the reach and sustainability of such measures, equitable insurance coverage should be available for the full spectrum of pain treatments, particularly as insurance initiatives have been shown to impact pain care access [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Virtual team models of care for CBP may be a potential solution to further explore. 42–44 Given that cost was a main challenge in accessing care, it is appropriate that more coordinated approaches for improvements include funding for mental health and physical therapies, incentivizing this high-value care.…”
Section: Discussionmentioning
confidence: 99%
“…Within chronic disease management education and occupational therapy, the majority of participants preferred virtual over in-person care, with the virtual care being feasible, accessible and easy to operate [14] , [15] . Virtual care in nutrition, nursing, and physical therapy has reduced in-person visits for individuals with chronic illnesses while maintaining clinical standards [16] , [17] . Although virtual care has been catalyzed from the pandemic, one report in the field of dermatology showed that a vast majority of patients will continue to prefer virtual care in a post pandemic world [18] .…”
Section: Discussionmentioning
confidence: 99%